Existence and concentration of positive solutions for a system of coupled saturable Schrödinger equations. (August 2020) - Lehrer, Raquel; Soares, Sergio H. Monari
Abstract: It is considered a saturable system of coupled Schrödinger equations with asymptotically linear nonlinearities. The bound states (solutions with finite energy) are proved to exist and have a concentration behavior under hypotheses involving the coupling and saturation parameters. The proof is based on variational methods.